A modified version of Jacobi approach. (27th August 2009) - Sarkar, Bikash Kanti; Sana, Shib Sankar; Mahanti, P.K.
Several well-known approaches exist to solve a set of linear equations. This short paper introduces a modified version of the existing sequential Jacobi iterative method. The prime contribution of the present investigation is that the variables which achieve smaller than the prescribed accuracy in the earlier iteration will not be updated further as before. Although these are updated in a simpler way to filter the non-converged variables, consequently, it reduces execution time to a great extent. Results demonstrate that the proposed approach outperforms the most of the linear sets.